2002
DOI: 10.1103/physrevd.65.065019
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium evolution in scalarO(N)models with spontaneous symmetry breaking

Abstract: We consider the out-of-equilibrium evolution of a classical condensate field and its quantum fluctuations for a scalar O(N) model with spontaneously broken symmetry. In contrast to previous studies we do not consider the large N limit, but the case of finite N , including N = 1, i.e., plain λφ 4 theory. The instabilities encountered in the one-loop approximation are prevented, as in the large-N limit, by back reaction of the fluctuations on themselves, or, equivalently, by including a resummation of bubble dia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 61 publications
(135 reference statements)
1
27
0
Order By: Relevance
“…At tree (classical) level this background results in different multiplet structures in the two sectors, but solving (81) iteratively one can show that the emerging exact mass spectra will have eventually the same structure in both sectors due to the coupling realised by the tensor H. To be specific, when v 3 = 0, v 8 = 0 one has 3 degenerate doublets in the "planes" [1,2], [4,5] and [6,7] and one coupled set with unequal eigenvalues in the [3,8] "plane". These "planes" correspond to the pairs of fields…”
Section: The Su (N ) × Su (N ) Meson Model In 2pi-hartree Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…At tree (classical) level this background results in different multiplet structures in the two sectors, but solving (81) iteratively one can show that the emerging exact mass spectra will have eventually the same structure in both sectors due to the coupling realised by the tensor H. To be specific, when v 3 = 0, v 8 = 0 one has 3 degenerate doublets in the "planes" [1,2], [4,5] and [6,7] and one coupled set with unequal eigenvalues in the [3,8] "plane". These "planes" correspond to the pairs of fields…”
Section: The Su (N ) × Su (N ) Meson Model In 2pi-hartree Approximationmentioning
confidence: 99%
“…Making use of the gap equation (8) for the sigma field in the equation of state (10), one immediately sees that for the consistent renormalisation of the two equations one has to require…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…These approximations have been extensively studied and their features are well known [11][12][13][14][15][16]: they do provide a backreaction term on the evolution of quantum fluctuations that stabilize dynamics at late time but, on the other hand, they fail to properly describe an important aspect of late-time dynamics such as thermalization. More elaborate approaches going beyond mean field have been put forward by considering the 2-particle-irreducible (2PI) or the two-point-particle-irreducible effective action [17,18] at two (or more) loops or at next-to-leading order in 1=N expansion [19][20][21][22], yielding indeed approximate numerical thermalization at strong coupling.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the squared mass of the "pion" modes starts to oscillate around the asymptotic zero value rather early, but the oscillations are damped only for asymptotically large times as t −1 . In a recent paper [8] renormalised non-equilibrium gap equations were solved for the effective mass-squares of the longitudinal and transversal modes propagating on a time dependent background. These masses were in earlier papers [9,10] with a self-consistent parametrisation of the corresponding propagators.…”
Section: Introductionmentioning
confidence: 99%